Roles of Microenvironment on Mesenchymal Stem Cells Therapy for Osteoarthritis - Zhang H; Jin C; Hua J; Chen Z; Gao W; Xu W; Zhou L; Shan L (Dove Medical Press, 2024)
Haiyan Zhang,1,* Chaoying Jin,2,* Jiaqing Hua,3,* Zuxiang Chen,4 Wenxin Gao,4 Wenting Xu,4 Li Zhou,4 Letian Shan1 1The Second Affiliated Hospital, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 2School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People's Republic of China; 3College of Pharmaceutical Science, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 4The First Affiliated Hospital, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Letian Shan; Li Zhou, Email letian.shan@zcmu.edu.cn; zhouli@zcmu.edu.cnAbstract: Osteoarthritis (OA) induced microenvironmental alterations are a common and unavoidable phenomenon that greatly exacerbate the pathologic process of OA. Imbalances in the synthesis and degradation of cartilage extracellular matrix (ECM) have been reported to be associated with an adverse microenvironment. Stem cell therapy is a promising treatment for OA, and mesenchymal stem cells (MSCs) are the main cell sources for this therapy. With multispectral differentiation and immunomodulation, MSCs can effectively regulate the microenvironment of articular cartilage, ameliorate inflammation, promote regeneration of damaged cartilage, and ultimately alleviate OA symptoms. However, the efficacy of MSCs in the treatment of OA is greatly influenced by articular cavity microenvironments. This article reviews the five microenvironments of OA articular cavity, including inflammatory microenvironment, senescence microenvironment, hypoxic microenvironment, high glucose microenvironment and high lipid environment, focus on the positive and negative effects of OA microenvironments on the fate of MSCs. In this regard, we emphasize the mechanisms of the current use of MSCs in OA treatment, as well as its limitations and challenges.Keywords: microenvironment, mesenchymal stem cells, osteoarthritis